Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Konsumen dan Dampaknya Pada Kepercayaan Konsumen Lazada - Wala Erpurini; Nur Alamsyah; Rimbun Kencana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of product quality and service quality on consumer satisfaction and the impact on Lazada consumers' trust at the Elzatta Hijab Official store. The population in this study were followers of the Elzatta Hijab Official store. The research method used is descriptive and associative methods. Where to test the influence between the independent variables and the dependent variable. The results of the research through descriptive analysis showed that product quality, service quality and consumer satisfaction and their impact on consumer confidence were in the very good category. The data analysis technique used is path analysis. Associative testing shows the effect of product quality on consumer satisfaction by 73.8%, the effect of service quality on consumer satisfaction by 22.3%. The effect of product quality and service quality on consumer satisfaction is 90.3%. The effect of product quality, service quality, and consumer satisfaction on consumer confidence is 64.8%.